2003
DOI: 10.1261/rna.2160803
|View full text |Cite
|
Sign up to set email alerts
|

RBP16 is a multifunctional gene regulatory protein involved in editing and stabilization of specific mitochondrial mRNAs in Trypanosoma brucei

Abstract: RBP16 is a Trypanosoma brucei mitochondrial RNA-binding protein that associates with guide RNAs (gRNAs), mRNAs, and ribosomal RNAs. Based on its inclusion in the multifunctional Y-box protein family and its ability to bind multiple RNA classes, we hypothesized that RBP16 plays a role in diverse aspects of mitochondrial gene regulation. To gain insight into RBP16 function, we generated cells expressing less than 10% of wild-type RBP16 levels by tetracycline-regulated RNA interference (RNAi). Poisoned primer ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
132
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(141 citation statements)
references
References 67 publications
9
132
0
Order By: Relevance
“…It may be that RNA editing of developmentally regulated transcripts requires the participation of specific protein factors that allow efficient gRNA/mRNA annealing. A number of gRNA binding proteins have been characterized that accelerate the hybridization of cognate guide RNA/pre-edited mRNA pairs [43][44][45][46]. Recently, Pelletier and Read [46] showed that RNAi knockdowns of the Y-box protein, RBP16, led to a 98% reduction in the levels of edited CYb mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that RNA editing of developmentally regulated transcripts requires the participation of specific protein factors that allow efficient gRNA/mRNA annealing. A number of gRNA binding proteins have been characterized that accelerate the hybridization of cognate guide RNA/pre-edited mRNA pairs [43][44][45][46]. Recently, Pelletier and Read [46] showed that RNAi knockdowns of the Y-box protein, RBP16, led to a 98% reduction in the levels of edited CYb mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…For northern blot analysis of edited RPS12 mRNA, a radiolabeled DNA probe corresponding to the fulllength fully edited RPS12 sequence was generated by PCR reaction using oligonucleotides CR6-5′T7 and CR6-3′E with [α-32 P]dATP, and hybridization was performed as described previously (17). Poisoned primer extensions using oligonucleotides Tub-RT, COI-RT, ND1-RT, ND4-RT, CO2-RT, CYb-RT, A6-3′NE, ND7-RT and COIII-3′NE were performed with 20 μg of total RNA as described previously (43). Gels were analyzed by phosphoimager analysis on a Bio-Rad Personal FX Phosphoimager using Quantity One software.…”
Section: Rna Analysismentioning
confidence: 99%
“…The final column summarizes the demonstrated (and proposed) roles in editing, as cited in the Introduction and the above references. mHel61p helicase of the z20S complex may aid removal of gRNAs after editing (Missel et al 1997); also proteins separate from the z20S complex can affect editing, including TbMP108/KRET1 (that adds U-tails onto gRNAs) (Aphasizhev et al 2002(Aphasizhev et al , 2003c, TbgBP21 and TbgBP25 (that stimulate RNA annealing) (Müller et al 2001;Müller and Göringer 2002;Aphasizhev et al 2003b;Schumacher et al 2006), REAP1 (a putative mRNA-binding protein) , and RBP16 (a CYb RNA factor) (Pelletier and Read 2003). …”
Section: Introductionmentioning
confidence: 99%